CCR7 Is Recruited to the Immunological Synapse, Acts as Co-stimulatory Molecule and Drives LFA-1 Clustering for Efficient T Cell Adhesion Through ZAP70 - Laufer, Julia M.; Kindinger, Ilona; Artinger, Marc; Pauli, Andreas; Legler, Daniel F. (Frontiers in Immunology, 2019)
The chemokine receptor CCR7 guides T cells and dendritic cells to and within lymph nodes to launch the onset of adaptive immunity. Here, we demonstrate that CCR7 in addition acts as a potent co-stimulatory molecule in T cell activation. We found that antigen recognition and engagement of the TCR results in CCR7 accumulation at the immunological synapse where CCR7 and the TCR co-localize within sub-synaptic vesicles. We demonstrate that CCR7 triggering alone is sufficient to recruit and activate ZAP70, a critical kinase for T cell activation, through Src kinase, whereas TCR CCR7 co-stimulation results in increased and prolonged ZAP70 kinase activity. Finally, we show that ZAP70, acting as adapter molecule, is critical for CCR7-mediated inside-out signaling to integrins, thereby modulating LFA-1 valency regulation to promote cell adhesion, a key step in immunological synapse formation and efficient T cell activation.